Upward movement of the ice sheet near the Yamato Mountains estimated from an ice core analysis (abstract) - Nakawo, Masayoshi; Nagoshi, Masayasu; Mae, Shinji (National Institute of Polar Research, 1989)
P(論文) Measurements of density, total gas content, departmental bulletin paper